From Herd Boy to University Lecturer: An Autobiography - Hara, Yotamu (MZUNI Press, 2019)
Cover -- Copyright page -- Title page -- Contents -- Preface -- Chapter 1: Birth and Boyhood of Handwell Yotamu Hara -- Chapter 2: Handwell Leaves for the Central Region -- Chapter 3: Handwell Goes back to School -- Chapter 4: Handwell's Married Life and his Theological Training -- Chapter 5: Handwell as Lecturer, Pastor and Doctoral Student (1981-1988) -- Chapter 6: Handwell as Education Secretary for Nkhoma Synod Schools -- Chapter 7: Handwell at ZTC, GMTI and Mzuzu University as a Lecturer -- Postscript -- Back cover.